Investigating the Impact of Flap Overdesign on Viability - Aherrera, Andrew S.; Pincus, David J.; Vernadakis, Adam J. (The Surgery Journal, 2016)
Background Partial or complete flap necrosis is a detrimental outcome complicating reconstructive surgery. The purpose of this study was to evaluate the impact of flap overdesign on viability in the rat model.Methods Forty Sprague-Dawley rats were equally divided into four groups receiving flaps of varying length-to-width ratios: 2:1, 3:1, 4:1, and 5:1. All animals had caudally based, modified McFarlane-style flap created. Areas of survival were assessed 14 days postoperatively and compared among groups using one-way analysis of variance.Results The mean areas of flap survival were 8.0 ± 0.0 cm2, 7.8 ± 1.1 cm2, 8.3 ± 1.1 cm2, and 8.1 ± 1.5 cm2 for the 2:1, 3:1, 4:1, and 5:1 length-to-width ratio groups, respectively. There were no statistically significant differences in mean areas of flap survival among groups (p > 0.05).Conclusion Flap overdesign does not increase the risk of flap necrosis in a random-pattern flap.
Keywords: flap; overdesign; flap necrosis; viability; reconstructive surgery; tissue defect